The Mediating Role of Networking Competence in The Relationship Between Market Knowledge Capability on SMES Performance - Yakin, Nur (Program MM Universitas Surabaya, 2023)
PurposeThis article investigated market knowledge capability’ role in enhancing performance and the impact of networking competence on SMEs’ performance.Method: The samples studied were 162 export-oriented furniture SMEs from Sukoharjo. The purposive sampling technique collected the data. Only 142 samples were declared complete and feasible to continue hypothesis testing. Structural Equation Modeling (SEM) was implemented to check the hypothesis model.Result: This study found that the market knowledge capability constructs positively and significantly affected SMEs’ performance. Market knowledge positively influenced networking competence, while networking competence positively and significantly affected SMEs’ performance.